Adalimumab, etanercept, infliximab, certolizumab pegol, golimumab, tocilizumab and abatacept for the treatment of rheumatoid arthritis not previously treated with disease-modifying antirheumatic drugs and after the failure of conventional disease-modifying antirheumatic drugs only : systematic review and economic evaluation /: systematic review and economic evaluation. (April 2016) - Stevenson, M (Matt)
No abstract available